Relationship between polypharmacy and inpatient hospitalization among older adults with cancer treated with intravenous chemotherapy. Issue 4 (May 2020) - Lu-Yao, Grace; Nightingale, Ginah; Nikita, Nikita; Keith, Scott; Gandhi, Krupa; Swartz, Kristine; Zinner, Ralph; Sharma, Swapnil; Kelly, W.M. Kevin; Chapman, Andrew
Abstract: Objectives: Polypharmacy (≥5 concurrent medications) is common among older patients with cancer (48%–80%) and associated with increased frailty, morbidity, and mortality. This study examined the relationship between polypharmacy and inpatient hospitalization among older adults with cancer treated with intravenous (IV) chemotherapy. Materials and Methods: The main data source was the Surveillance, Epidemiology, and End Results-Medicare linked files. Patients (≥65 years) were included if they were diagnosed with prostate ( n = 1430), breast ( n = 5490), or lung cancer ( n = 7309) in 1991–2013 and received IV chemotherapy in 2011–2014. The number of medications during the six-month window pre-IV chemotherapy initiation determined polypharmacy status. Negative binomial models were used to assess the association between polypharmacy and post-chemotherapy inpatient hospitalization. The results were presented as incidence rate ratios. Results: We identified 13, 959 patients with prostate, breast, or lung cancer treated with IV chemotherapy. The median number of prescription medications during the six-month window pre-IV chemotherapy initiation was high: ten among patients with prostate cancer, nine among patients with breast cancer, and eleven among patients with lung cancer. Compared to patients taking <5 prescriptions, post-chemotherapy hospitalization rate for patients with prostate cancer was 42%, 75%, and 114% higher among those taking 5–9, 10–14, and 15+ medications, respectively. Patients with breast and lung cancer demonstrated similar patterns. Conclusion: This large population-based study found that polypharmacy during the six-month window pre-IV chemotherapy is highly predictive of post-chemotherapy inpatient hospitalization. Further studies are needed to evaluate whether medication management interventions can reduce post-chemotherapy inpatient hospitalization among older patients with cancer.